Stiffness-based design-oriented compressive stress-strain model for large-rupture-strain (LRS) FRP-confined concrete. (1st September 2019) - Bai, Yu-Lei; Dai, Jian-Guo; Mohammadi, Mohsen; Lin, Guan; Mei, Shi-Jie
Abstract: Large rupture strain fiber-reinforced polymers (LRS FRPs) (e.g., with an elongation larger than 5%) provide ideal confinement for seismic retrofit of concrete columns. Most of existing design-oriented models for FRP-confined concrete define the slope of axial stress-strain curve (i.e., axial stiffness) as a function of FRP's rupture strain. Consequently, concrete confined with FRP of the same jacket stiffness but different rupture strains usually lead to different axial stiffnesses, which is contrary to the experimental observations. For LRS FRP-confined concrete a slight deviation in the axial stiffness might cause significant error in predicting its ultimate state. Therefore, a design-oriented model is developed here to define axial stiffness using the jacket stiffness rather than its rupture strain. 26 LRS FRP-confined circular concrete cylinders are tested and added to a database of 36 existing specimens. Then an existing lateral-to-axial strain (dilation) relationship is upgraded based on the above database and a database on 113 conventional FRP-confined concrete cylinders. A three-fold approach is employed to define the full-range stress-strain relation of LRS FRP-confined concrete as a function of jacket stiffness. The proposed stiffness-based design-oriented model predicts both softening and hardening behaviors and is applicable to both conventional and LRS FRP-confined concrete columns.